Adaptation technologies for climate-smart agriculture: a patent network analysis - Tey, Yeong Sheng; Brindal, Mark; Darham, Suryani; Zainalabidin, Syahaneem Mohamad (Springer Science and Business Media LLC, 2024)
Global interest in innovative adaptation approaches in climate-smart agriculture is growing, and adaptation technologies are expanding. This study investigates technological developments in agricultural adaptation innovation through an analysis of specific technology classifications in a global patent database. Patent keyword co-occurrence network analyses show that greenhouse technologies have received increased R&D attention, while early composting processing technologies have evolved into organic fertilizer product innovation. Biotechnology has been another area of R&D, seeking desirable traits suited to the changing climatic conditions. Resource restoration innovations have recently emerged. Addressing climate challenges, these technologies broaden climate-smart agriculture policy options, from general to specific operations. They provide the means for integration with nature-based adaptation strategies, but their diffusion (and hence potential) may be limited by the path dependence of ownership. While commercialization will continue to drive innovation diffusion, international cooperation is desirable to better facilitate technology transfer. Future efforts are recommended to reduce the complexity of climate-smart agriculture. As technology becomes more available and integrated with nature-based solutions, it is our recommendation that policymakers and governments should consistently seek to reduce impediments to an exchange of knowledge.